Characterisation of volatiles in dried white varieties figs (Ficus carica L.) - Mujić, Ibrahim (Springer India, 2012)
The aromatic profile of volatiles in dried figs varieties Bružetka Bijela and Zimnica were characterised by headspace solid-phase (HS-SPME) procedure with gas chromatography–mass spectrometry analysis (GC-MS). The volatile compounds were distributed by distinct chemical classes, including alcohols, aldehydes, esters, terpenic compounds, and other compounds. The figs were dried in a pilot plant cabinet dryer. Prior to drying process, figs were pre-treated by sulphur dioxide, immersed in solution of citric acid and ascorbic acid, respectively. Several mathematical thin-layer drying models, available in the literature, were fitted to experimental data of figs, implementing non-linear regression analysis techniques. The results showed that pre-treatments of figs decrease significantly the drying time. The best thin-layer drying model in terms of fitting performance was Wang and Singh model. The major volatile compound in dried figs was benzaldehyde. After benzaldehyde, the most abundant aldehyde in dried figs was hexanal. The comparison among dried figs showed the highest abundance of aldehydes, in general, in non-treated (control) dried figs compared to pre-treated samples. Furthermore, ascorbic acid was the most efficient in preserving esters and alcohols in case of Bružetka Bijela, whereas in case of Zimnica, sulphur dioxide was in advance compared to ascorbic acid. Ethyl acetate was the most abundant ester found in dried figs. Among other compounds, 2-butanone,3-hydroxy was the most abundant identified volatiles. Linalool, as the only identified terpen, was in case of both dried fig varieties, preserved by immersion into ascorbic acid. The immersion into citric acid has not been so successful in volatiles conservation.